Chicago schools old and new on the efficacy of monetary policy - TAVLAS, G.S. (PSL Quarterly Review, 2013)
This paper traces the evolvement of monetary-policy proposals at Chicago from the early 1930s up until the appearance of Friedman’s classic “Restatement” of the quantity theory in 1956. First, the pragmatic nature of Chicagoan monetary economics during the depression-dominated 1930s is examined. The emergence of the Chicagoan affirmation in the efficiency of traditional monetary policy is then described. It is argued that rather than representing a transmogrification of the monetary views of his predecessors, Friedman’s “Restatement” more accurately reflects a culmination of post-Keynesian Chicago contributions on money. In addition, the interpretation of budget deficits financed by money creation as the implementation of monetary, as opposed to fiscal, policy is shown to be a common link among Chicagoans throughout the entire period under consideration. JEL: E51, E52, E40